ANALISIS PERENCANAAN PAJAK PENGHASILAN ATAS PENGEMBANGAN INVESTASI BIDANG PROPERTI - Natalia Kartika; Heru Tjaraka (Jurnal Ekonomi dan Bisnis Airlangga, 2018)
Business investment in property is very promising and could be an asset in the future because the price of land and buildings continue increasing. Many entrepreneurs are interested in investing in property but it is not an easy thing. For entrepreneurs who have investment opportunities but do not have sufficient funds or assets or otherwise, can be empowered by getting its business partners for mutual investment through the establishment of a new business entity. The establishment of business entities is certainly not free from income tax aspects. Income taxes are expenses that reduce income earned by entrepreneurs. Therefore tax planning is necessary in order to save costs without violating applicable regulations. Selection in the establishment of business entities is one way to do tax planning. The right selection in establishment of business entities can give tax savings without violating applicable regulations. This study aims to determine the income tax planning analysis of the development of property investment, if done with the establishment of joint operation (JO) or forming a Limited Liability Company (PT). This study used a qualitative research approach with the strategy used in this research is a case study on PT X and PT Y. The results of the analysis and discussion shows that the burden of income tax to be paid by PT X and PT Y will be lower when it is done with the establishment of a joint operation (JO) than if it is done with the establishment of a Limited Liability Company (PT).